Palaeoenvironmental evidence for the impact of the crusades on the local and regional environment of medieval (13th–16th century) northern Latvia, eastern Baltic. (January 2016) - Stivrins, Normunds; Brown, Alex; Veski, Siim; Ratniece, Vita; Heinsalu, Atko; Austin, Jennifer; Liiv, Merlin; Ceriņa, Aija
This paper evaluates the impact of the crusades on the landscape and environment of northern Latvia between the 13th–16th centuries (medieval Livonia). The crusades replaced tribal societies in the eastern Baltic with a religious state (Ordenstaat) run by the military orders and their allies, accompanied by significant social, cultural and economic developments. These changes have previously received little consideration in palaeoenvironmental studies of past land use in the eastern Baltic region, but are fundamental to understanding the development and expansion of a European Christian identity. Sediment cores from Lake Trikāta, located adjacent to a medieval castle and settlement, were studied using pollen, macrofossils, loss-on-ignition and magnetic susceptibility. Our results show that despite continuous agricultural land use from 500 BC, the local landscape was still densely wooded until the start of the crusades in AD 1198 when a diversified pattern of pasture, meadow and arable land use was established. Colonisation followed the crusades, although in Livonia this occurred on a much smaller scale than in the rest of the Ordenstaat; Trikāta is atypical showing significant impact following the crusades with many other palaeoenvironmental studies only revealing more limited impact from the 14th century and later. Subsequent wars and changes in political control in the post-medieval period had little apparent effect on agricultural land use.